Achievement and Growth for English Learners. Issue 4 (June 2023) - Johnson, Angela
This study reports achievement and growth from kindergarten to fourth grade for three groups of English Learners (ELs): (a) ever-ELs; (b) ELs consistently eligible for service; and (c) EL and Special Education dually-identified students. All three EL groups had lower test scores than never-ELs throughout K-4. In math, ELs grew more than never-ELs during academic years but lost more during summers. In reading, ELs grew less than never-ELs in K-1 and grew more in later grades, but ELs also lost more during summers. These findings suggest summer support is required to help ELs maintain and develop academic skills.